Genetic Landscape of Slovenians: Past Admixture and Natural Selection Pattern - Maisano Delser, Pierpaolo; Ravnik-Glavač, Metka; Gasparini, Paolo; Glavač, Damjan; Mezzavilla, Massimo (Frontiers in Genetics, 2018)
The Slovenian territory played a crucial role in the past serving as gateway for several human migrations. Previous studies used Slovenians as a source population to interpret different demographic events happened in Europe but not much is known about the genetic background and the demographic history of this population. Here, we analysed genome-wide data from 96 individuals to shed light on the genetic role and history of the Slovenian population. Y chromosome diversity splits into two major haplogroups R1b and R1a with the latter suggesting a genetic contribution from the steppe. Slovenian individuals are more closely related to Northern and Eastern European populations than Southern European populations even though they are geographically closer. This pattern is confirmed by an admixture and clustering analysis. We also identified a single stream of admixture events between the Slovenians with Sardinians and Russians around 2630 BCE (2149-3112). Using ancient samples, we found a significant admixture event between the Yamnaya and the early Neolithic Hungarians dated around 1762 BCE (1099-2426) suggesting a strong contribution from the steppe to the foundation of the observed modern genetic diversity. Finally, we looked for signals of selection in candidate variants and we found significant hits in HERC2 and FADS when compared to Southern Europeans responsible for blue eye colour and synthesis of long-chain unsaturated fatty acids respectively. When the comparison was done with Eastern Europeans, we identified significant signals in PKD2L1 and IL6R which are genes associated with taste and coronary artery disease respectively.